The banshees of Inisherin - Burwell, Carter 1954- (The Walt Disney Company Limited, 2023)
"From the writer and driector of Three billboards and In Bruges: From writer-director Martin McDonagh (Three Billboards Outside Ebbing, Missouri) comes a unique film starring Colin Farrell and Brendan Gleeson. Although Pádraic (Farrell) and Colm (Gleeson) have been lifelong friends, they find themselves at an impasse when one abruptly ends their relationship, bringing alarming consequences for both of them." (DVD-Rückseite)
Spielfilm
Original: Irland/Großbritannien/USA 2022
Bildformat 2.39:1
Warnhinweise/Altersempfehlung: "strong language, injury detail, domestic abuse", "Suitable only for persons of 15 years and over. Not to be supplied to any person below that age." (DVD-Hülle)
Alterseinstufung des "Irish Film Classification Office": 15 ("Fit for viewing by persons aged 15 years or more")
Keywords: Male friendship -- Drama; Islands -- Ireland -- Social conditions -- 20th century -- Drama; Interpersonal relations -- Drama; Self-destructive behavior -- Drama; 1900-1999; Islands - Social conditions; Male friendship; Dark comedy films; Drama; Feature films; Fiction films; Video recordings for people with visual disabilities; Video recordings for the hearing impaired; Comedy films; Historical films; Ireland; Film; DVD-Video